Hippocampal kindling in rats with absence epilepsy resembles amygdaloid kindling - ONAT, FİLİZ; GÜLHAN, REZZAN (ELSEVIER, 2008)
Purpose: WAG/Rij and GAERS rats show delays or resistance to secondary generalization of limbic seizures during amygdaloid kindling. In this study, we aimed to evaluate the kindling from a different limbic site, hippocampus, and to compare its effects on spike-and-wave discharges (SWDs) with that of amygdaloid kindling. Methods: Recording electrodes were implanted epidurally and a stimulation/recording electrode was implanted into the ventral hippocampus in the WAG/Rij, GAERS and Wistar rats. Animals received kindling stimulation twice daily at their afterdischarge thresholds until they reached stage 5 seizures, or the maximum number of stimulations (50) had been delivered. The EEG was recorded to analyze SWDs and afterdischarge durations. Results: All Wistar rats reached stage 5 by the 34th stimulation. 4 of 8 WAG/Rij rats and 3 of 6 GAERS rats displayed stage 4/5 seizures (kindling-prone rats); the rest stayed at stage 2 seizures (kindling-resistant rats) even after 50th stimulations. The cumulative duration and number of SWDs decreased in the post-stimulation period after the first stage 2 seizures, whereas these parameters increased after the first stage 3 seizures in the kindling-prone WAG/Rij and GAERS. The peak frequency of SWDs and its harmonics decreased significantly only in the GAERS group after stage 4 seizures. Conclusion: Hippocampal kindling resembles amygdaloid kindling in showing a delay of or resistance to secondary seizure generalization, which supported the interaction of thalamo-cortical and limbic circuitry in GAERS and WAG/Rij. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Generalized epilepsy; WAG/Rij; GAERS; Temporal lobe epilepsy model; Partial epilepsy; Kindling resistance; NUCLEUS-REUNIENS-THALAMI; FERRITIN HEAVY-CHAIN; ELECTRICAL-STIMULATION; BIDIRECTIONAL TRANSFER; PERIRHINAL CORTEX; SEIZURES; BRAIN; MECHANISMS; EXPRESSION; MODEL